Relationship among Test Anxiety, Study Habit and Self-Efficacy on Academic Achievement of Senior Secondary School Students in FCT, Abuja, Nigeria - Gidado, Bello Kumo; Lasisi, Kasim (Kashere Journal of Education, 2025)
This study investigated the relationship among anxiety, study habits, self-efficacy, and academic achievement of senior secondary school students in the Federal Capital Territory (FCT), Abuja, Nigeria. Five objectives, five research questions, and five hypotheses were formulated to guide the study. A correlational survey research design was adopted for the study. The sample consisted of three hundred eighty-two (382) students chosen from a total population of 66,390 senior secondary school students. A simple random sampling technique was employed for the study. The instrument used for data collection was a self-structured questionnaire titled ’Relationship among Anxiety, Study Habits, and Self-Efficacy’. Students’ achievement was measured using scores from the Senior Secondary School Education Board. The questionnaire was validated by experts in measurement and evaluation, while a pilot test was conducted with a reliability coefficient of 0.82. The collected data were analysed using a mean score and standard deviation for the research questions, while the Pearson Product Moment Correlation Coefficient (PPMCC) and multiple regression were used to test the hypotheses. The findings revealed that there was no significant difference in students’ anxiety levels based on gender. The study also revealed that there was a significant difference in students’ study habits due to gender. The study further found a significant relationship between anxiety and academic achievement, as well as a significant relationship between self-efficacy and academic achievement among senior secondary school students in FCT, Abuja. Based on these findings, it was recommended that guidance and counselling services should be made readily available and functional in schools to provide students with proper academic direction, thereby reducing academic stress and anxiety.